Degradation mechanism and kinetic model for photocatalytic oxidation of PVC-ZnO composite film in presence of a sensitizing dye and UV radiation - Sampa, Chakrabarti (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2008)
White or plastic pollution has become a serious concern to the environmentalists for the last few years. Degradation of waste plastics in conventional incinerators leads to emission of carcinogenic dioxins to the atmosphere. In this work, an attempt has been made for the photocatalytic degradation of polyvinyl chloride (PVC) using ZnO as semi-conductor catalyst in the form of PVC-ZnO composite film. The surface morphology as well as the FTIR spectroscopy of the irradiated film has been critically examined. The degradation was measured by weight loss data and was found to follow a pseudo-first order rate equation. The various parameters studied were loading of the semi-conductor, intensity of UV radiation and presence of Eosin Y as a sensitizing dye. It was observed that dye-sensitization enhanced degradation of PVC to a large extent. A possible mechanism has been suggested and the corresponding rate equation has been modeled for the dye-sensitized rate of degradation. The model has been validated by the experimental data. (C) 2007 Elsevier B.V. All rights reserved.